PENGARUH PENGEMBANGAN KARIR DAN PEMBERIAN INSENTIF TERHADAP LOYALITAS KARYAWAN RADAR BROMO PROBOLINGGO (JAWA POS GRUP) - Amirah Hanin; Abdul Kadir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe aim of this research is to identify and explain about career development, giving incentive, and employee loyalty. Moreover, this study is identify about the influence of career development, giving incentive toward employee loyalty parsially or simultaneously. The sample of this research is all Radar Bromo Prolinggo Jawa Timur’s employee that contain 59 employee using census method. In this method, all the data was collected by using questionnaire and statistically analyzed using multiple linier regressions with applying SPSS 22.0 for Windows. The research method that used in this research is quantitative research method with the explanatory type of research. The result of this research showed that career development have significant influence toward employee loyalty and incentive awarding parsially as well as career development and giving incentives significantly influence simultaneously toward employee loyalty.Keywords: employee loyalty, career development, and gIving incentive.